(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
Developing and implementing steps to provide financial support to the agriculture industry is crucial. Specifically, it is suitable to allocate funds from the subsidy programme towards supporting animal husbandry, horticulture, vegetable cultivation, greenhouse operations, poultry farming, and related sectors. Regarding credit allocation, the state provides long-term preferential loans and leases to the agricultural sector through commercial banks. Additionally, commercial banks receive reimbursement from state funds for a specific period of time to partially cover the loans they assign.